The Oeuvre of Jan Alan Bardziński – a Dominican, Preacher and Translator - Rusnak, Radosław (Tematy i Konteksty, 2021)
The article is devoted to little known and rarely appreciated late-Baroque Dominican Jan Alan Bardziński who was a keen preacher and translator of both secular and religious texts. Bardziński’s literary activity is strongly connected to his duties performed in the order as one of the main values he searches for in his texts is of a didactic nature. Simultaneously, he may certainly be perceived as an adapter of some ancient works which puts him among other 17th and 18th-century followers of the culture of Classicism. In the article we briefly discuss his works and provide the readers with their distinctive features. Moreover, we shall take into consideration Bardziński’s notes which allow us to define his goals and priorities and underline the moral values included in his works.